Mission unstoppable - Gutman, Dan. (New York : Harper, 2011)
On a cross-country vacation with their parents, twins Coke and Pepsi, soon to be thirteen, fend off strange assassins as they try to come to terms with their being part of a top-secret government organization known as The Genius Files.
MSBA Nominee 2012-13.
Keywords: Genius -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Twins -- Juvenile fiction; Assassins -- Juvenile fiction; Recreational vehicles -- Juvenile fiction; Families -- Juvenile fiction; Adventure fiction